Pengaruh Program Hutan Kemasyarakatan (HKm) Terhadap Kesejahteraan Masyarakat Kelompook Tani Hutan Batu Kura di Desa Galam Kceamatan Bajuin Menggunakan Metode Partial Least Square (PLS) - Ayu Yunita Lolo; Muhammad Naparin; Syam'ani Syam'ani (Universitas Lambung Mangkurat, 2024)
ABSTRACT, An ecosystem with vast expanses of land where the dominant natural resources are composed of interconnected trees that are inseparable from their environment is called a forest. Forests are regulated by the government to provide positive impacts on sustainable forest management to ensure their continued utilization. Forests also play a role as managers of various cycles and providers of various natural resources needed by humans. The social forestry program has been implemented throughout the archipelago, including in South Kalimantan. Galam Village, located in the Bajuin District of Tanah Laut Regency, is one of the villages that has developed a social forestry program under the Community Forest (HKm) scheme and formed the Batu Kura Forest Farmers Group. Since the issuance of the Community Forest management permit by the Ministry of Environment and Forestry, the Batu Kura Forest Farmers Group has been engaged in HKm activities, focusing on the production of non-timber forest products, specifically candlenut fruit, which has been actively produced since 2019.ABSTRAK. Ekosistem yang memiliki hamparan lahan yang luas dimana dominasi sumber daya alam hayati yang tersusun di dalamnya berupa pepohonan yang memiliki hubungan dengan alam lingkungannya dan tidak bisa dipisahkan merupakan hutan. Hutan diatur oleh pemerintah untuk menyediakan dampak positif terhadap pengelolaan hutan secara lestari agar tetap dapat dimanfaatkan hasilnya. Hutan juga berperan sebagai pengelola berbagai siklus sekaligus penyedia berbagai kebutuhan sumber daya alam yang dibutuhkan oleh manusia. Program dari perhutanan sosial telah dilaksanakan di seluruh Nusantara termasuk di Kalimantan Selatan. Desa Galam Kecamatan Bajuin yang berada dalam wilayah Kabupaten Tanah Laut merupakan salah satu dari Desa yang telah mengembangkan program dari perhutanan sosial dengan skema Hutan Kemasyarakatan (HKm) dan membentuk Kelompok Tani Hutan Batu Kura. Sejak penerbitan SK izin pengelolaan Hutan Kemasyarakatan dikeluarkan oleh Kementerian Lingkungan Hidup dan Kehutanan, KTH Batu Kura memulai kegiatan HKm dengan memproduksi hasil hutan bukan kayu berupa buah kemiri yang aktif diproduksi sejak tahun 2019.